Using Fuzzy Cognitive Maps to Reduce False Alerts in SOM based Intrusion Detection Sensors - Jazzar, Mahmoud; Jantan, Aman
Most of the intrusion detection sensors suffer from the high rate offake alerts that the sensor produce.